2021
DOI: 10.3390/agronomy11112139
|View full text |Cite
|
Sign up to set email alerts
|

Contrary to Red, Blue Monochromatic Light Improves the Bioactive Compound Content in Broccoli Sprouts

Abstract: Broccoli sprouts are rich in health-promoting bioactive compounds. Their content depends on both cultivation light quality and temperature. However, these effects have been previously addressed in isolation. Here, the dual inputs of cultivation light quality [blue (B), red (R), mixture of R and B (R+B), mixture of R and UVA (R+UVA)] and air temperature (15, 19, and 23 °C) on determining growth, external quality, and the cotyledon and hypocotyl content of five major bioactive compounds were investigated. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Contrarily, in the work of Maina et al [ 31 ], both blue and red LEDs enhanced the accumulation of sinigrin in Ethiopian mustard, where especially the red LEDs were also effective in increasing the accumulation of 4-hydroxyglucobrassicin, 4-methoxyglucobrassicin, and neoglucobrassicin (while decreasing the levels of glucobrassicin), in concordance with our results. However, we also found that the use of blue LEDs produced better results than red LEDs for black mustard sprouts, as previously determined, for example, in broccoli sprouts [ 25 ]. A significant positive effect of blue LEDs on the biosynthesis of aliphatic glucosinolates in broccoli sprouts has been related with the overexpression of the CYP79F1 and CYP83A1 genes that are involved in their biosynthesis pathway [ 43 ], which may be extended to other species.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Contrarily, in the work of Maina et al [ 31 ], both blue and red LEDs enhanced the accumulation of sinigrin in Ethiopian mustard, where especially the red LEDs were also effective in increasing the accumulation of 4-hydroxyglucobrassicin, 4-methoxyglucobrassicin, and neoglucobrassicin (while decreasing the levels of glucobrassicin), in concordance with our results. However, we also found that the use of blue LEDs produced better results than red LEDs for black mustard sprouts, as previously determined, for example, in broccoli sprouts [ 25 ]. A significant positive effect of blue LEDs on the biosynthesis of aliphatic glucosinolates in broccoli sprouts has been related with the overexpression of the CYP79F1 and CYP83A1 genes that are involved in their biosynthesis pathway [ 43 ], which may be extended to other species.…”
Section: Resultssupporting
confidence: 87%
“…Previous works have reported that the use of either monochromatic blue or red LEDs may affect several growth parameters in broccoli sprouts, but did not produce a biomass increase [ 24 , 25 ]. Neither the supplementation of warm-white light with blue or red LEDs (50 µmol m −2 s −1 ) was effective for increasing the biomass in baby-leaf lettuce [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). The level of primary energy reserves has been earlier associated with prolonged postharvest longevity 22 , 37 . For instance, an increased content of soluble carbohydrates may support maintenance needs (by sustaining ATP synthesis), and protect membrane integrity (by scavenging reactive oxygen species) 22 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…As a sensitive indicator of photosynthetic performance, dark-adapted values of the maximum quantum yield of PSII (F v /F m ; equation and explanation in Table 3 ) were non-invasively recorded in leaves of each treatment 22 , 37 , 63 . Measurements were performed by using a portable imaging fluorometer (Handy FluorCam FC 1000-H, Photon Systems Instruments, Drásov, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%